Pulmonary toxicity, genotoxicity, and carcinogenicity evaluation of molybdenum, lithium, and tungsten: A review. (15th February 2022) - Hadrup, Niels; Sørli, Jorid B.; Sharma, Anoop K.
Abstract: Molybdenum, lithium, and tungsten are constituents of many products, and exposure to these elements potentially occurs at work. Therefore it is important to determine at what levels they are toxic, and thus we set out to review their pulmonary toxicity, genotoxicity, and carcinogenicity. After pulmonary exposure, molybdenum and tungsten are increased in multiple tissues; data on the distribution of lithium are limited. Excretion of all three elements is both via faeces and urine. Molybdenum trioxide exerted pulmonary toxicity in a 2-year inhalation study in rats and mice with a lowest-observed-adverse-effect concentration (LOAEC) of 6.6 mg Mo/m 3 . Lithium chloride had a LOAEC of 1.9 mg Li/m 3 after subacute inhalation in rabbits. Tungsten oxide nanoparticles resulted in a no-observed-adverse-effect concentration (NOAEC) of 5 mg/m 3 after inhalation in hamsters. In another study, tungsten blue oxide had a LOAEC of 63 mg W/m 3 in rats. Concerning genotoxicity, for molybdenum, the in vivo genotoxicity after inhalation remains unknown; however, there was some evidence of carcinogenicity of molybdenum trioxide. The data on the genotoxicity of lithium are equivocal, and one carcinogenicity study was negative. Tungsten seems to have a genotoxic potential, but the data on carcinogenicity are equivocal. In conclusion, for all three elements, dose descriptors for inhalation toxicity were identified, and the potential for genotoxicity and carcinogenicity was assessed.